Church Community Music Activities and the Benefits for Participants. Issue 1 (2nd January 2021) - de Villiers, Alethea; Rossouw, Carolyn
Abstract: Community Music (hereafter CM) exists in many forms, including choral groups, instrumentalists, bands and other ensembles. The literature on community music highlights how participants in different contexts benefit from participating in community music activities. This article reports on a study in which the researchers investigated diverse forms of CM in three church settings in Port Elizabeth (now Gqeberha), Eastern Cape, South Africa. These church CM activities included a senior adult choir, a youth band, and an instrumental ensemble. A multiple case study approach was followed and data was collected through observations, unstructured interviews, audio and written materials. The thematic analysis revealed that participation in CM activities had a positive effect on the participants.